Recombinant human transforming growth factor-alpha stimulates the formation of osteoclast-like cells in long-term human marrow cultures. - Takahashi, N (1986)
Transforming growth factor-alpha (TGF-alpha) is synthesized by a variety of tumor cell lines and stimulates osteoclastic bone resorption in vitro. The mechanism by which TGF-alpha increases osteoclast activity is unknown. We used a human marrow culture system that forms osteoclast-like multinucleated cells (MNCs) to determine the effects of recombinant human TGF-alpha on MNC formation. Addition of 0.01 ng/ml TGF-alpha for the 1st week followed by 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] for the subsequent 2 wk significantly increased MNCs. Treatment of these cultures with TGF-alpha without later addition of 1,25(OH)2D3 did not increase MNC formation. Autoradiographic studies revealed that TGF-alpha stimulated proliferation of precursors for MNCs, and 1,25(OH)2D3 increased their rate of fusion into MNCs. Addition of murine epidermal growth factor (EGF) (0.1 ng/ml) followed by 1,25(OH)2D3 also significantly stimulated MNC formation. These data suggest that TGF-alpha and EGF may stimulate bone resorption by increasing the proliferation of osteoclast precursors, which leads to increased numbers of osteoclasts.